ORGANISATION OF SEED PRODUCTION IN ALL-RUSSIAN RESEARCH INSTITUTE OF VEGETABLE BREEDING AND SEED PRODUCTION - V. F. Pivovarov; S. M. Sirota (Овощи России, 2012)
The results of VNIISSOK reproduction of vegetable seeds are given. The basic problems in seed production of vegetable crops are shown.